Organic and conventional food: Comparison and future research. (February 2019) - Suciu, Nicoleta Alina; Ferrari, Federico; Trevisan, Marco
Abstract: Background: Organic food is generally considered as having healthier properties as consequence of the environmental-friendly management if compared with conventional food. However, there is a lack of strong scientific evidences that organic food is significantly different from the conventional regarding nutritional properties, environmental and human health impacts. Scope and approach: The main scope of the present review is to assess the differences between the organic and conventional food in terms of nutritional properties, environmental impact and consumer perception and to identify future research needed. Key findings and conclusions: Nutritional properties, the "environmental friendly" concept and the consumer perception aspects were analyzed to compare organic and conventional food. In general, non-significant differences in nutrient properties and carbon food prints between organic and conventional food have been observed, even if for the both aspects significant sensitivity and uncertainty are present and specific analysis to assess them are mandatory. Consumers perceive the organic food more valued even if relatively higher prices and poorer availability of organic products compared with their conventional counterparts could limit the purchase and the quality perception. Highlights: Differences between organic and conventional food is a continue debate. No weighty nutritional and "eco-friendly" differences between organic and conventional food were scientifically demonstrated. Organic food is more valued by consumers. High sensitivity and uncertainty of scientific results should be considered in the future research.